Nahdlatul Ulama and Digital Civil Society in the Post-Truth Era: Contesting Moderate Islamic Narratives on Social Media - Deryl Ardica; Muhammad Syaf'ul Iktafi; Agus Nurwansyah (Lakpesdam PCNU Kota Salatiga, 2026)
This article examines the framing contestation surrounding Nahdlatul Ulama (NU) within Indonesia’s post-truth digital environment. Employing framing theory, information disorder frameworks, and communication power theory, this study analyzes how NU is represented, contested, and negotiated across social media platforms. Through qualitative document analysis and systematic literature review, three dominant competing frames are identified: the moderate-nationalist frame promoted by NU’s official digital ecosystem, the radical-opposition frame constructed by conservative Islamist networks, and the populist-identity frame deployed by political actors for electoral mobilization. The study finds that post-truth conditions, algorithmic amplification, and networked disinformation campaigns create structurally asymmetric conditions that disadvantage NU’s moderate Islamic narratives. In response, NU has developed multifaceted counter-narrative strategies encompassing institutional digital platforms such as NU Online, media literacy programs within pesantren communities, creative da‘wa content production, and collaborative regulatory engagement with state institutions. The article argues that NU increasingly functions as a significant digital civil society actor whose communication strategies contribute to the preservation of democratic discourse and religious moderation in Indonesia. These findings offer broader insights into how large-scale Islamic organizations navigate digitally mediated information disorders while maintaining commitments to democratic pluralism and social cohesion.